2005
DOI: 10.1111/j.1399-0012.2005.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized trial of steroid withdrawal in kidney recipients treated with mycophenolate mofetil and cyclosporine

Abstract: Steroid withdrawal in low risk kidney transplant recipients is safe and ameliorates many of the unwanted sides effects of steroid use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Similar results were observed in a subset of patients in the study by Pelletier et al (35,36), in whom BMD in both the spine and hip increased in the steroid withdrawal group during the first year after withdrawal. No significant change was seen in the patients continuing steroids.…”
Section: Other Outcomessupporting
confidence: 86%
“…Similar results were observed in a subset of patients in the study by Pelletier et al (35,36), in whom BMD in both the spine and hip increased in the steroid withdrawal group during the first year after withdrawal. No significant change was seen in the patients continuing steroids.…”
Section: Other Outcomessupporting
confidence: 86%
“…We included nine RCTs including 1820 patients assessing SW compared with steroid maintenance in patients with MMF or MFS as a third drug (11)(12)(13)(14)(15)(16)(17)(18)(19). None included mammalian target of rapamycin (mTOR) inhibitors.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…A single-center trial comparing steroid withdrawal versus maintenance steroids with MMF and cyclosporine therapy indicated that there was no difference in the incidence of NODAT. However, corticosteroid weaning was only started approximately 450 days after transplantation, and NODAT was reported in only 10/118 (8.5%) of patients (16). In the FREEDOM study, recipients were randomized to steroids, no steroids, or steroids to day 7 with maintenance therapy consisting of cyclosporine, mycophenolate sodium and basiliximab induction (17).…”
Section: Discussionmentioning
confidence: 99%